MR Analysis of the Substantia Innominata in Normal Aging, Alzheimer Disease, and Other Types of Dementia - Hanyu, Haruo; Asano, Tetsuichi; Sakurai, Hirofumi; Tanaka, Yuriko; Takasaki, Masaru; Abe, Kimihiko (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: The substantia innominata can be visualized on coronal thin-section T2-weighted MR images. The purpose of this study was to investigate the morphologic changes of the substantia innominata in normal aging by using MR imaging and to determine whether the changes in this structure on MR images were specific to Alzheimer disease (AD).METHODS: The thickness of the substantia innominata was measured on the coronal T2-weighted image obtained through the anterior commissure in 39 healthy control subjects (age range, 25–86 y; mean age, 62 y); 39 patients with AD; and 36 patients with non-AD dementia, including vascular dementia, frontotemporal dementia, and Parkinson disease with dementia.RESULTS: In the control subjects, the thickness of the substantia innominata significantly decreased with age. Compared with age-matched control subjects, both patients with AD and patients with non-AD dementia had significant atrophy of the substantia innominata. The thickness of the substantia innominata significantly correlated with scores from the Mini-Mental State Examination in patients with AD but not in patients with non-AD dementia.CONCLUSION: MR analysis reveals age-related shrinkage of the substantia innominata. Atrophy of the substantia innominata, which reflects degeneration in the nucleus basalis of Meynert, is pronounced both in patients with AD and in those with non-AD dementia. MR imaging features in this structure may not be specific to AD.